The Merck manual of diagnosis and therapy - Beers, Mark H.;Robert S. Porter;Thomas V. Jones;Justin L. Kaplan;Michael Berkwits (New Jersey : Merck Research Laboratories, 2006)
Written by more than 300 experts in various fields of medicine, the 18th Edition of The Merck Manual provides even more explicit guidance on the diagnosis and treatment of medical conditions. With its expanded clinical focus, the Manual helps readers keep pace with advancements and changes to the medical landscape.
Includes index.
Keywords: DIAGNOSIS -- DICTIONARIES